Museum Balaputra Dewa sebagai Sarana Pembelajaran Interaktif bagi Guru Sejarah di Kota Palembang - Darme, Made; Kurniawati, Kurniawati; Marta, Nur Aeni (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This research aims to analyze, evaluate, and assess history teachers in using the Balaputra Dewa Museum as a source of history learning. The research method used is qualitative with a descriptive analysis approach, which includes data condensation, data presentation, and conclusions from the results of data analysis which are strengthened through further verification. The results of this research show that the Balaputra Dewa Museum is a historical learning resource that is utilized by history teachers by inviting students to produce a learning process that makes it easier to understand history more effectively. Apart from that, students are more enthusiastic about learning because they feel less pressured and learn more freely. Through learning from the Balaputra Dewa Museum, students can enrich their knowledge, national insight, identity, and uphold a sense of nationalism. The benefits of learning history at the Balaputra Dewa Museum through historical remains have enabled students to recognize the history of their region so that the museum has become a very important learning place for the world of education.